The Impact of Currency Derivatives on Firm Value for Malaysian Corporates - Sagathavan, Naveen (2014)
Since the Ringgit was de-pegged in the middle of June 2005, the awareness for Malaysian corporates to hedge its currency position has increased steadily. Past research works on the effects of hedging using derivatives on firm value remains mixed. The aim of this study is to find out the impact of currency derivatives usage on firm value in the context of Malaysian companies, utilizing a sample size of 20 non-financial firms, represented approximately 50% of the top 100 companies in term of market capitalization on Bursa Malaysia from the year 2006 to 2012, as at 1st January 2013. All data compiled were secondary in nature from companies’ annual reports. This research paper also extended its study to investigate the effect of foreign exchange derivatives based on the samples selected on firm value before (2006 & 2007), during (2008 & 2009) and after the global financial crisis (2010-2012). The investigation concluded that currency derivatives usage does not significantly influence firm value. Meanwhile, on the control variables, dividend per share and return of assets are positively correlated with firm value while being statistically significant, suggest that the bigger the dividend payout to shareholders, the higher the firm value. Meanwhile, for profitability, represented by return of asset, indicated that the more profitable a company is, the firm value will also increase alongside. Currency derivatives impact on firm value pre-crisis and during the global financial meltdown, the findings showed a positive relationship despite being statistically insignificant, while post global financial crisis, the relationship turned negative. The US Federal Reserve launched quantitative easing program to boost the US economy which subsequently weakened the Dollar and strengthened the Asian currencies on the back of the monetary policy action which resulted in Malaysian firms reducing its hedging needs. However, the relationship was statistically insignificant.